(untitled) (Global Journal of Management and Business Research, 2022)
In this article we present a mathematical model of asset allocation to an investment portfolio that optimizes the returns obtained under a series of restrictions. Said allocation is made between a group of companies in the Eurostoxx 50 index that are preselected based on the evolution of their accounting and financial variables. We tested this investment method in the period 2009-2019 and compared the evolution of the profitability and volatility of the portfolio obtained with respect to the Eurostoxx 50 index